Adult Diapause in Coleoptera - Ivo Hodek (Psyche: A Journal of Entomology)
Recent studies dealing with adult (reproductive) diapause in the Coleoptera are reviewed, as a kind of supplement to the classic compendia. In the first two sections, the general characteristics of adult diapause are described and principal terms explained. Original articles dealing with 19 species from nine coleopteran families (Coccinellidae, Chrysomelidae, Bruchidae, Curculionidae, Carabidae, Silphidae, Scolytidae, Scarabaeidae, and Endomychidae) are reviewed. Finally attempts are made at generalisations from the papers reviewed, and hypotheses on diapause evolution are inferred. A polyphenic character of diapause is a prominent feature in C. septempunctata and L. decemlineata, but has been found also in other Coleoptera and in insects generally and often generates voltinism heterogeneity within populations.